Development, Characterization, and Comparative Analysis of Halal-Compliant Fortified Caulerpa lentillifera Jelly with Enhanced Nutritional and Antioxidant Properties - Nor Atikah Husna Ahmad Nasir; Mohd Hafis Yuswan; Nor Nadiah Abd Karim Shah; Kaiser Mahmood; Aswir Abd Rashed; Kazunori Kadota; Yus Aniza Yusof (Journal of Healthcare and Biomedical Science, 2026)
Oxidative stress is linked to many chronic diseases, making antioxidant-rich functional foods important for health. This study aims to evaluate the nutritional composition and antioxidant capacity of fortified C. lentillifera jelly (FJ), control jelly (CJ), and commercial jelly (MJ) using mineral analysis, proximate analysis, and antioxidant assays, followed by Principal Component Analysis (PCA). The fortified jelly, formulated without gelatin or other non-Halal ingredients, ensures compliance with Halal dietary requirements while maintaining desirable product characteristics. The results showed that FJ exhibited enhanced antioxidant activity, with DPPH and ABTS scavenging capacities of 68% and 45%, respectively. These antioxidant activities indicate the ability of the fortified jelly to scavenge free radicals, which are implicated in cellular damage and oxidative stress-related diseases. In addition, FJ had lower sodium content than MJ, suggesting its potential as a healthier alternative. The relatively lower moisture content in FJ (50.34%) compared to MJ (88.28%) contributed to a higher concentration of nutrients and carbohydrates within the product matrix. PCA explained 97.4% of the total variance, clearly differentiating the jelly samples based on their compositional attributes. PC1 was primarily associated with potassium, fat, and ash, while PC2 was influenced by antioxidant activity and selected minerals, including magnesium and zinc, which were more prominent in FJ. Overall, these findings suggest that C. lentillifera-fortified jelly may help reduce oxidative stress and support better health as a Halal functional food.